Estudo comparativo sobre o uso da glicose a 25% para redução da dor em recém-nascido a termo submetidos à injeção intramuscular da vitamina k - ANDRADE, Emanoelle Cardoso de Oliveira (2019)
The treatment of neonatal pain is a challenge to health professionals. This pain of invasive procedures in the first hour care in the delivery room, either by manipulation or the application of vitamin K to prevent hemorrhagic disease, among other causes. The administration of vitamin K, although painful, is rarely accompanied by as analgesic. Objective: To compare the efficacy of glucose 25% in pain scores in infants born at term, underwent intramuscular administration of vitamin K. Thus evaluating the efficacy of glucose solution in 25% pain relief by administering a single dose of 1 ml two minutes before the painful procedure. Methods: Randomized clinical trial, conducted at the first aid room newborn Maternity Child Health in October 2011. The sample consisted of 150 infants, of which 75 randomized in the experimental group (glucose) and 75 in the control group. Two minutes before being subjected to an intramuscular injection of vitamin K, the experimental group received 1 mL of 25% glucose orally. The primary endpoint was the assessment of heart rate, oxygen saturation, followed by scales: Neonatal Infant Pain Scale (NIPS), Premature Infant Paint Profile (PIPP) and Behavioral Indicators of Infant Pain (biip). The research project was approved by the ethics committee of the Faculty of Nursing (Research Ethics Committee-CEP). Results: ANOVA showed that the change in heart rate were less marked in the group receiving 25% glucose, as well as the change in oxygen saturation, thus following, the other one. Glucose 25% was effective for the relief of pain in newborns undergoing painful procedures term administration of vitamin K. Conclusion: The measure of analgesic oral glucose 25% was effective for the treatment of acute pain caused by intramuscular administration of vitamin K.